2020
DOI: 10.1016/j.ophtha.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Vascular Endothelial Growth Factor Use and Atrophy in Neovascular Age-Related Macular Degeneration

Abstract: Topic: To summarize the rates of atrophy, risk factors, and atrophy-associated visual outcomes in patients with neovascular age-related macular degeneration (nAMD) who received antievascular endothelial growth factor (VEGF) treatment for macular neovascularization (MNV).Clinical Relevance: Age-related macular degeneration is a leading cause of vision loss worldwide, and VEGF inhibitors are the primary treatment for nAMD. However, atrophy is observed frequently in eyes treated with anti-VEGF therapy, prompting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
(93 reference statements)
1
42
1
Order By: Relevance
“…Finally, the association with the development of atrophy and anti-VEGF use has been hotly debated in recent years, but this study found no significant association between the development of atrophy and anti-VEGF exposure or MNV growth variables [46]. Though a clear correlation with the development of atrophy was not expected, it is possible that macular atrophy was under identified since, for some subjects, analysis was restricted to 3 × 3 mm images, the length of follow-up may not have been long enough to detect this effect, and the type and amount of anti-VEGF treatment may be different than other studies that have suggested this association.…”
Section: Discussioncontrasting
confidence: 66%
“…Finally, the association with the development of atrophy and anti-VEGF use has been hotly debated in recent years, but this study found no significant association between the development of atrophy and anti-VEGF exposure or MNV growth variables [46]. Though a clear correlation with the development of atrophy was not expected, it is possible that macular atrophy was under identified since, for some subjects, analysis was restricted to 3 × 3 mm images, the length of follow-up may not have been long enough to detect this effect, and the type and amount of anti-VEGF treatment may be different than other studies that have suggested this association.…”
Section: Discussioncontrasting
confidence: 66%
“…56,57 Sadda et al reported that it is important to recognize that adequately treating nAMD remains the best option to optimize visual outcomes in patients, particularly given the risk of vision loss with under-treatment observed in the real-world. 59 Mones et al 60 suggest that better long-term visual outcomes could be achieved by changing the community mindset that contributes to under-treatment of this chronic disease. Other reasons initial gains may wane over time include loss of patient enthusiasm for frequent treatment and also the progressive onset of atrophic AMD.…”
Section: Long-term Visual Outcomes (>2 Years)mentioning
confidence: 99%
“… 5 – 7 Distinctive clinical characteristics of RPD are the typical incomplete or complete ring-shaped pattern with initial sparing of the fovea in contrast to soft drusen, which are typically located in central retinal areas, as well as the higher associated risk of progression to late stages including atrophy development. 8 12 Moreover, a higher incidence of RPD and development of multifocal lesions of macular neovascularization type 3 (MNV 3) has been recently described, which were typically more likely distributed in the temporal perifoveal area corresponding to the predominant pattern of RPD distribution. 13 , 14 In this context Sadda and coworkers 12 demonstrated in a meta-analysis that atrophy development often occurred in context of MNV treated with anti-vascular endothelial growth factor (VEGF) therapy; however, at the same time it remained unclear whether anti-VEGF treatment is a causal reason for atrophy or rather associated with atrophy development.…”
mentioning
confidence: 99%
“… 8 12 Moreover, a higher incidence of RPD and development of multifocal lesions of macular neovascularization type 3 (MNV 3) has been recently described, which were typically more likely distributed in the temporal perifoveal area corresponding to the predominant pattern of RPD distribution. 13 , 14 In this context Sadda and coworkers 12 demonstrated in a meta-analysis that atrophy development often occurred in context of MNV treated with anti-vascular endothelial growth factor (VEGF) therapy; however, at the same time it remained unclear whether anti-VEGF treatment is a causal reason for atrophy or rather associated with atrophy development. Besides RPD counting as a high-risk factor for retinal atrophy and corresponding progressive visual impairment, a putative association of RPD and systemic cardiovascular diseases has been suggested in previous studies.…”
mentioning
confidence: 99%